Decreased amygdala–insula resting state connectivity in behaviorally and emotionally dysregulated youth. Issue 1 (30th January 2015) - Bebko, Genna; Bertocci, Michele; Chase, Henry; Dwojak, Amanda; Bonar, Lisa; Almeida, Jorge; Perlman, Susan Beth; Versace, Amelia; Schirda, Claudiu; Travis, Michael; Gill, Mary Kay; Demeter, Christine; et al.
Abstract: The Research Domain Criteria (RDoC) adopts a dimensional approach for examining pathophysiological processes underlying categorically defined psychiatric diagnoses. We used this framework to examine relationships among symptom dimensions, diagnostic categories, and resting state connectivity in behaviorally and emotionally dysregulated youth selected from the Longitudinal Assessment of Manic Symptoms study ( n =42) and healthy control youth ( n =18). Region of interest analyses examined relationships among resting state connectivity, symptom dimensions (behavioral and emotional dysregulation measured with the Parent General Behavior Inventory-10 Item Mania Scale [PGBI-10M]; dimensional severity measures of mania, depression, anxiety), and diagnostic categories (Bipolar Spectrum Disorders, Attention Deficit Hyperactivity Disorder, Anxiety Disorders, and Disruptive Behavior Disorders). After adjusting for demographic variables, two dimensional measures showed significant inverse relationships with resting state connectivity, regardless of diagnosis: 1) PGBI-10M with amygdala–left posterior insula/bilateral putamen; and 2) depressive symptoms with amygdala–right posterior insula connectivity. Diagnostic categories showed no significant relationships with resting state connectivity. Resting state connectivity between amygdala and posterior insula decreased with increasing severity of behavioral and emotional dysregulation and depression; this suggests an intrinsic functional uncoupling of key neural regions supporting emotion processing and regulation. These findings support the RDoC dimensional approach for characterizing pathophysiologic processes that cut across different psychiatric disorders. Highlights: Examined resting state in behaviorally/emotionally dysregulated youth. Recruited participants from Longitudinal Assessment of Manic Symptoms (LAMS) study. Decreased resting state connectivity associated with greater depressive symptoms. Resting state connectivity negatively related to behavioral/emotional dysregulation. Supports Research Domain Criteria (RDoC) dimensional approach.